FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT KEPATUHAN WAJIB PAJAK (Studi Kasus Wajib Pajak OP Pelaku e-commerce di Kota Malang) - Qisthi Yoeanda; Afifudin Afifudin; Muhammad Cholid Mawardi (Universitas Islam Malang, 2018)
ABSTRACTThis study aims to analyze the factors that influence taxpayer compliance,namely the awareness of taxpayers, taxation sanctions, and understanding oftaxation. The population of this study was determined based on purposivesampling method, the data was collected by distributing online questionnaires, ecommerce players who made trading sales through the Market Place Shopeeapplication domiciled in Malang City, had> 1000 followers, and had manypositive reviews from customers who became source of data of the author in thestudy.The research analysis method used is multiple linear regression. Based onthe results of the analysis shows that the awareness of taxpayers has a positiveand significant effect on taxpayer compliance, tax sanctions have a positive andsignificant impact on taxpayer compliance, understanding taxation has a positiveand significant impact on taxpayer compliance.The most dominant factor affecting taxpayer compliance is the awarenessof taxpayers because it has a standard coefficient value of 0.476 beta.Keywords : Taxpayer Awareness, Tax Sanctions, Taxpayer Compliance andTaxpayer Compliance